FREQUENCY DEPENDENCE OF THE IONOSPHERE SCINTILLATION PARAMETERS ON THE OBSERVATIONS OF COSMIC RADIO SOURCES AT THE DECAMETER WAVE RANGE - Panishko, S K.; Lytvynenko, O. A. (Одеські астрономічні публікації, 2019)
When signal from radio source propagates through irregularity layer in the ionosphere it has fluctuations of the amplitude (scintillations) which time spectrum has power form with index α = 3. It was shown that such form of the time spectrum of amplitude fluctuations caused by power form of the spatial spectrum of electron concentration ionosphere irregularity with index ρ = α + 1, i.e. ρ = 4. Based on theoretical preconditions for such form of the spatial spectrum the frequency dependence of scintillation index m (scintillation intensity characteristic) was obtained in form power function: m ∝ f −n , n = (ρ + 2) 4 ⁄ , thus n= 1.5. Similar frequency dependence of the scintillation index was observed experimentally for case of weak scintillations (m < 0.5). In this work the frequency dependence of scintillation parameters was analyzed on long-term observations of power cosmic radio sources on radio telescope URAN-4 at 20 and 25 MHz. The results were compared with results of earlier carried out investigations.